2021
DOI: 10.1097/md.0000000000026467
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant melanoma of the esophagogastric junction

Abstract: Rationale: Most gastrointestinal melanomas are metastatic from an oculocutaneous primary lesion; however, primary gastrointestinal melanomas have been found in all levels of the gastrointestinal tract. We present the case of Primary malignant melanoma of the esophagus and discuss the diagnostic methods, differentiation from metastatic lesions and treatment options. Patient concerns: A 78-year-old male patient presented with fresh blood vomiting and tarry stools for 1 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The patient received 30 courses of nivolumab and has maintained the partial response without severe adverse events. These data are very similar to those of the paper of Chu et al [ 292 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The patient received 30 courses of nivolumab and has maintained the partial response without severe adverse events. These data are very similar to those of the paper of Chu et al [ 292 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although Nivolumab has been shown to be less effective in mucosal melanomas than in cutaneous melanomas, the standard treatment and efficacy of ICI in PMME remain unclear due to its rarity [ 275 , 288 , 289 , 290 , 291 , 292 , 293 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 ]. As we have analyzed, some studies have revealed promising results, but there is a need for randomized controlled trials with larger series of PMME patients [ 186 , 218 , 275 , 305 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few cases of primary GI melanomas have been reported in the literature and are believed to arise from ectopic melanocytes [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma is a disease with poor prognosis that develops from melanocytes of the skin, oral cavity, nasal cavity, pharynx, uvea, and rectum. Primary melanoma of the gastrointestinal tract is rare [ 1 – 3 ], particularly in patients with melanoma esophagogastric junction of which there has been few case reports [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%